Student Teams Achievement Type Cooperative Learning Model Division for Increase Results Learn Math on Student - Wassar, Ena Natalia; Subhanudin, Subhanudin; Rasul, A (Lembaga Intelektual Muda (LIM) Maluku, 2021)
This study aims to improve mathematics learning outcomes in Grade VII students of SMP N 10 Mimika with use method Problem based Learning (PBL). Study this is study class action, which was carried out in two cycles where the first cycle consisted of 4 meetings and II consists of 5 meetings the subjects in this study were grade VII students. A which amounts to 29 students. The variables in this study consisted of independent variables, namely the Problem Based Learning method (PBL) and the dependent variable is the result of learning mathematics, technical data collection using Data Analysis Techniques, namely analysis of observation results and analysis of test results. Based on research results could concluded that learning with method Problem based Learning (PBL) could increase results study on eye lesson mathematics on Theory arithmetic social, results before action was taken, namely in the pre-cycle only 8 students or 27.58% which is completed in cycle I increase Becomes 24 student or 82.75% which finished study mathematics and on cycle II increase again Becomes 29 student which finished study mathematics, research this said succeed because reach indicator performance that is 100% from whole student with KKM that is 60